Minat Membaca dan Motivasi Belajar Dalam Meningkatkan Indeks Prestasi - Supomo Supomo (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to determine the Effect of Reading Interest (X1), Learning Motivation (X2) and is in the process of determining Reading Interest (X1), Learning Motivation (X2) Against Learning Achievement Grade XI IPA2 Students in Sorong 1 Public High School (Y) ) This type of research is Ex post facto. Purposive sampling is a sampling technique used in this study. The interest and motivation of learning to read have a significant influence on the achievement index of students in class XI IPA2 of Sorong City Senior High School 1, respectively at 70.1% and 67.6%. Taken together the interest in reading and learning motivation has a significant influence on the achievement index of students in class XI IPA2 in Sorong City 1 Public High School, amounting to 74.8%.